English English - Alamanda, Firas; Maryani, Enok; Sopandi, Wahyu; Sujana, Atep (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
This research is undermined by Indonesia's low economic independence index, which will be only 23.3% by 2022. It shows that people do not understand finance enough in terms of knowledge, attitudes, and skills to plan, manage, record, and store financial data. The method used is case studies, with data collection techniques through observations, interviews, and documentation. The subject of the study was 23 students in Bandung City. Descriptive analysis to interpret the data. Research results show that financial literacy through the RADEC model shows excellent results. Students can study the learning material with extensive resources before entering the class in the reading and answering phase. Financial literacy, which involves acquiring, spending, holding, and donating, can be integrated into material needs, desires, and abilities. The RADEC model stage gives students the opportunity to acquire and build their own knowledge either individually by visiting various resources or through discussions both within and among groups.